Conditions of smoothness for the distribution density of a solution of a multidimensional linear stochastic differential equation with levy noise - Bodnarchuk, S. V.; Kulik, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
A sufficient condition is obtained for smoothness of the density of distribution for a multidimensional Levy-driven Ornstein-Uhlenbeck process, i.e., a solution to a linear stochastic differential equation with Levy noise.